Phytic acid-modified manganese dioxide nanoparticles oligomer for magnetic resonance imaging and targeting therapy of osteosarcoma - Qian Ju; Rong Huang; Ruimin Hu; Junjie Fan; Dinglin Zhang; Jun Ding; Rong Li (Drug Delivery, 2023)
AbstractOsteosarcoma is the most common malignant tumor in the skeletal system with high mortality. Phytic acid (PA) is a natural compound extracted from plant seeds, which shows certain antitumor activity and good bone targeting ability. To develop a novel theranostics for magnetic resonance imaging (MRI) and targeting therapy of osteosarcoma, we employed PA to modify manganese dioxide nanoparticles (MnO2@PA NPs) for osteosarcoma treatment. The MnO2 NPs oligomer was formed by PA modification with uniformed size distribution and negative zeta potential. Fourier-transform infrared spectroscopy, X-ray diffraction, energy dispersive spectroscopy, X-ray photoelectron spectroscopy, and thermogravimetric analysis demonstrated that PA has been successfully modified on MnO2 NPs, and the structure of MnO2@PA NPs is amorphous. In vitro experiments demonstrated that MnO2@PA NPs oligomer can be efficiently internalized by tumor cell, and the internalized NPs can react with H2O2 under acid microenvironment to produce Mn2+ and O2. In vivo experiments demonstrated that MnO2@PA NPs oligomer can passively accumulate in tumor tissue, and the accumulated NPs can produce Mn2+ and O2 for MRI and targeting therapy of osteosarcoma. In conclusion, we prepared a novel bone-targeting nano theranostics for MRI and therapy of osteosarcoma.